A contrastive study of categories of complaints of Malaysian and American customers on facebook / Siti Aishah Mohd Rosdy - Siti Aishah, Mohd Rosdy (2017)
Studies of customer complaints are associated with the identification and analysis of all aspects involved in the customer response to a product or a service failure which brings about the feeling of dissatisfaction. The act of complaining can be defined as the way to express feelings of discontentment about something. This study, conducted on Malaysian and American customers is a cross-cultural pragmatic study of the speech act of online complaints. Data for this study is gathered from the most visited social-networking site, Facebook. The study intends to look at the significant differences in the expression of online complaints as realized by Malaysian and American Facebook users (customers). Using the taxonomy of complaint categories proposed by Olshtain and Weinbach (1987) and House and Kasper’s (1981) taxonomy of directness level, the complaint categories and level of directness of the online customer complaints are examined in this study. Findings show that there are similarities and differences in the realizations of online complaints by Malaysians and Americans. Americans tend to produce complaints which are longer in words as compared to Malaysians. Apart from that, American customers are found to be more direct than Malaysian customers in communicating their online complaints. Both Malaysian and American customers do not only use the modality markers to mitigate their complaints but they also use these linguistic markers to increase the impact of the complaint towards the complainee.